The effects of pre-obesity on quality of life, disease activity, and functional status in patients with ankylosing spondylitis (vol 4, pg 52, 2017) - Toy, Seyma; Ozbag, Davut; Altay, Zuhal; Kavakli, Ahmet (Kare Publ, 2021)
[Abstract Not Available]